The impact of corporate social responsibility on loyalty in the hotel sector : DOI: 10.5937/etp2503015P - Popović, Biljana; Radivojević, Nikola; Burnać, Vinko (Ekonomija - teorija i praksa, 2025)
The growing awareness of the broader social community about the importance of socially responsible activities has led to socially responsible behavior of organizations becoming not just a desirable choice, but an expected one. As a multidimensional concept, Corporate Social Responsibility (CSR) is most often observed within the context of its effects, one of the most significant being its influence on consumer behavior-specifically, their intentions to revisit the hotel and/or share positive experiences with others. Therefore, the aim of this paper is to examine the direct impact of CSR on customer loyalty, and then to explore the mediating effects of key factors identified in the literature that shape users’ perceptions of hotel services: service quality, corporate image, corporate reputation, and satisfaction, on the relationship between CSR and customer loyalty in the hotel industry. The research results indicate that CSR has a significant, positive, and direct effect on customer loyalty, which is mediated by service quality, corporate image, corporate reputation, and satisfaction, with service quality emerging as the strongest interaction factor.